Use Of Language Variations On Tiktok Social Media In Generation Z - Kusyairi; Hikmah; Nurul Qomariyah (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2024)
This article reviews how the use of Indonesian language in TikTok social media through several accounts of young people in generation Z. Where this tiktok media is used as a means to display his identity as a slang young person in social media with the use of language variations that are sociolect language variations.  This study aims to determine the use of language used by generation Z young people in every upload of TikTok video posts, captions used and comments made by netizens. This research uses a method with a type of literature study research which is then used for data collection. Based on the results of the study, it can be concluded that the analysis of the use of language variations on TikTok social media of generation Z young people found several language variations such as acrolec variations, vulgarity, slang, colloquial, jargon, and ken in several posts, captions and in the comment column. Caused by two factors, namely internal factors and external factors. In internal factors, language variation is formed through phonological and morphological processes. The external factors behind the use of language variations are informal or informal speech situations, the age of TikTok users who are still dominated by teenagers, the goals to be achieved by speakers, and differences in education and work levels.